Developing a quick guide on presenting data and uncertainty. (11th September 2017) - Lickiss, Matthew; Mulder, Kelsey J.; Black, Alison; Charlton‐Perez, Andrew J.; McCloy, Rachel A.; Chandler, Richard
Abstract : This paper describes the rationale, development and testing of a quick guide leaflet on the presentation of data and uncertainty. While tools for capturing, analysing and presenting data become more advanced, the fundamentals of presenting data with adequate context and clarity remain unchanged. The leaflet, aimed at scientists generating and presenting data, was created as part of an interdisciplinary collaboration (meteorologists, information designers, psychologists) working within the PURE Network project RACER, funded by the UK Natural Environment Research Council. A copy of the leaflet is included in this article.